Economic Evaluation of Nirmatrelvir/Ritonavir Among Adults Against Hospitalization During the Omicron Dominated Period in Malaysia: A Real-World Evidence Perspective - Ee Vien Low; Hoon Shien Teh; Nicholas Yee Liang Hing; Suresh Kumar Chidambaram; Mohan Dass Pathmanathan; Wee Ric Kim; Wei Jia Lee; Zhi Wei Teh; Maheshwara Rao Appannan; Shahanizan Mohd Zin; Faizah Muhamad Zin; Samha Bashirah Mohamed Amin; et al. (Adis, Springer Healthcare, 2024)
Abstract Background and objectives Nirmatrelvir/ritonavir was administered orally to manage mild to moderate symptoms of COVID-19 in adult patients. The objectives of this study were to (i) evaluate the cost-effectiveness of prescribing nirmatrelvir/ritonavir within 5 days of a COVID-19 illness in order to avert hospitalization within a 30-day period in the Malaysia setting; (ii) determine how variations in pricing and hospitalization rates will affect the cost-effectiveness of nirmatrelvir/ritonavir. Methods The 30-day hospitalization related to COVID-19 was determined using 1 to 1 propensity score-matched real-world data in Malaysia from 14 July 2022 to 14 November 2022. To determine the total per-person costs related to COVID-19, we added the cost of drug (nirmatrelvir/ritonavir or control), clinic visits and inpatient care. Incremental cost-effectiveness ratio (ICER) per hospitalization averted was calculated. Results Our cohort included 31,487 patients. The rate of hospitalization within 30 days was found to be 0.35% for the group treated with nirmatrelvir/ritonavir, and 0.52% for the control group. The nirmatrelvir/ritonavir group cost an additional MYR 1,625.72 (USD 358.88) per patient. This treatment also resulted in a reduction of 0.17% risk for hospitalization, which corresponded to an ICER of MYR 946,801.26 (USD 209,006.90) per hospitalization averted. Conclusion In Malaysia, where vaccination rates were high, nirmatrelvir/ritonavir has been shown to be beneficial in the outpatient treatment of adults with COVID-19 who have risk factors; however, it was only marginally cost effective against hospitalization for healthy adults during the Omicron period.